Molecular phylogenetic and morphological studies reveal increased species diversity in the millipede genus Skleroprotopus Attems, 1901 in China (Julida: Mongoliulidae) - Rong Chen; Yi Zhao; Sergei Golovatch; Wei-Xin Liu (Arthropod Systematics & Phylogeny)
A taxonomic study of the genus Skleroprotopus Attems, 1901 from nine provinces in China was conducted utilizing morphological comparisons and molecular phylogenetic analyses. The results reveal thirteen new species, i.e. Skleroprotopus yutiantianae sp. nov., S. tiankeng sp. nov., S. megistus sp. nov., S. penglai sp. nov., S. longissimus sp. nov., S. genjudi sp. nov., S. laiyuanensis sp. nov., S. longiflagellatus sp. nov., S. change sp. nov., S. ampullaceus sp. nov., S. incisodentatus sp. nov., S. multistriatus sp. nov., and S. conicus sp. nov. This significantly enriches the diversity of Skleroprotopus in China, bringing it to a total of 18 species. With the exception of S. yutiantianae sp. nov., all these species were collected in caves. In terms of their degree of adaptation to the cave environment, the latter six species are presumed troglophiles, while the others are likely troglobites. DNA-barcoding based on the COI mitochondrial gene is documented for the first time in this genus. The specific p-distances between Skleroprotopus species range from 6.6–17.0%, while intraspecific p-distances are only 0.2–1.4%. Additionally, the morphological features of male leg-pair 1, the penis and leg-pair 7 are also discussed.